Effect of preharvest applications of salicylic acid, CPPU, CaCl2 and neemazal on storage behaviour of nectarine cv. Snow Queen - Abrol, Ghan Shyam; Thakur, Kamal Singh (Journal of Postharvest Technology, 2018)
The present study was conducted to assess the effect of preharvest application of growth regulators, nutrients and fungicides on storage behaviour of nectarine fruit. All the preharvest treatments showed a beneficial effect on physico-chemical, antioxidant and sensory parameter of fruits in comparison to control. Among the preharvest treatments, calcium chloride @ 1.5 per cent, Neemazal @0.45 per cent, salicylic acid @3000 ppm and CPPU @15 ppm proved to be most effective in maintaining fruit quality and minimizing deterioration during 28 days storage at 3 ±1 ºC. CPPU @15 ppm, was the most effective treatment in maintaing fruit size, weight and antioxidant compounds viz. ascorbic acid and total phenol content in fruits. However, CaCl2 treatment @ 1.5 per cent proved to be the most effective in reducing physiological loss in weight and minimizing deterioration in fruit quality and in retaining maximum firmness during 28 days storage period.